The families SHARE project: novel insights on recruiting and engaging Black men in a community-based genomic education program - Julia R. Nummelin; Jama J. Brookes; Raegan A. Bishop; Calandra G. Whitted; Chiranjeev Dash; Laura M. Koehly (BMC Public Health)
Abstract Background Black Americans are disproportionately affected by a number of common complex conditions, such as cancer. Genomic tools like Family Health History (FHH) can be useful in guiding screening and behavior based on a person’s risk for these conditions. Factors such as family communication and societal norms can influence individuals’ knowledge of their FHH. Men, particularly Black men, are less likely than women to know FHH. Further, there is limited understanding of Black men’s participation in FHH dissemination, as they are often underrepresented in biomedical research. Understanding Black men’s perceptions of FHH sharing may help guide effective recruitment and retention efforts in future genomic research providing an opportunity to investigate their lack of engagement in FHH conversations. Aims The purpose of this paper was two-fold: (1) Detail methods that were effective in recruiting and retaining Black men in community-based genomic research interventions, and (2) Evaluate the factors influencing men’s participation in FHH gathering and sharing. Methods This one-year, mixed methods study combined qualitative community-based education programs (n = 12) and semi-structured interviews (n = 27), with quantitative survey assessing participant characteristics and sex differences (n = 50). Transcripts from the program were coded by separate study team members for themes and provided insights into study participants’ perceptions about FHH and their involvement in gathering and disseminating this information within their family. Results Challenges in recruiting and retaining Black men prompted the study team to pivot recruitment strategies, including partnering with community-based organizations focused on men’s health, growing the research team to include Black men, adapting to potential participants’ time constraints, and creating opportunities to build trust. A thematic analysis of community education sessions and interviews identified five themes, including social role expectations and perceived family disconnectedness, that provide insights into potential barriers to participation. Qualitative data from participants suggests that beliefs and perceptions about the roles Black men play in health discussions within the family may influence their involvement, while community programs were seen as encouraging men to engage in these conversations. Conclusion These lessons learned provide valuable perspectives on potential barriers to participation, which may inform future strategies that aim to engage Black men in family-oriented community education programs and genomic research.